ANALISIS TINGKAT KOGNITIF SOAL BUKU TEKS MATEMATIKA SMA/MA KELAS XII TERBITAN KEMENDIKBUD REVISI 2018 MATERI STATISTIKA BERDASARKAN TAKSONOMI BLOOM REVISI - Pratiwi, Monica Celine (Math Educa Journal, 2021)
The aim of this research was to determine the distribution of the cognitive levels on problem questions and competency test questions of statistics chapter in the mathematics textbook of Senior High School for 12th grade published by the Ministry of Education and Culture revised edition of the 2018 based on the revised of Bloom’s taxonomy. The revised of Bloom’s Taxonomy used was the cognitive process dimension which consists of: remembering (C1), understanding (C2), applying (C3), analyzing (C4), evaluating (C5), and creating (C6). This type of research is descriptive research with the research method used is qualitative research. The data collection technique in this research is using the documentation technique. Sources of research data in this research were problem questions and competency test questions of statistics chapter in the mathematics textbook of 12th Grade revised edition of the 2018. The exercise questions and the competency test questions had 45 questions with the distribution of the cognitive levels are remembering (C1) has 2 questions (4,4%), understanding (C2) has 12 questions (26,7%), applying (C3) has 23 questions (51,1%), analyzing (C4) has 4 questions (8,9%), evaluating (C5) has 4 questions (8,9%), and creating (C6) has 1 question (2,2%). Thus, the distribution of cognitive levels of problem questions and competency tests on statistical material is not proportional.